AN ANALYSIS OF HUMOROUS SPOOF TEXTS IN ENGLISH LANGUAGE TEXTBOOK: FLOUTING MAXIM, FORM AND FUNCTION - Wattimury, Eliezer; Maruanaya, Hendrik; Lekatompessy, Felicia (Pattimura University, 2024)
The research aims (1) To find types of maxims flouted by the character to create humor in Spoof text in english textbook entitled “Look Ahead 2” Year XI (2) To find the forms of humor found inside of spoof text in english textbook entitled “Look Ahead 2” Year XI (3) To find the function of humor in spoof text created by flouting the maxims. This research employs the descriptive qualitative method. The six spoof texts were analyzed by Reading, Analyzing and Concluding the data in accordance with the research objectives, and research questions. Furthermore, this study employed Data analysis techniques as proposed by Miles and Huberman (1994): Data Reduction, Data Display and Conclusion Drawing to analyze the flouting of maxims, forms of humor and functions of humor appearing in conversation between characters on the six spoof texts. Findings on the first research question revealed that there were flouting of maxims occurred in all six spoof texts, including flouting of maxim of quantity, maxim of quality, maxim of relation and maxim of manner to create humorous conversation. The second finding shows that there were four forms of humor found including irony (cosmic irony and verbal irony), satire, parody, pun and self-deprecation as the result of flouting maxim. findings on the third research question showed the functions of humor which were satire, parody and lastly entertainment. In conclusion, all types of maxims are found flouted by several forms of humor with few functions of humor. Following that, the researcher suggests students, teachers and future researchers to broaden their perspective and knowledge about humor in linguistics, especially about spoof texts.